Statins as first-line therapy for acute coronary syndrome? - Ostadal, Petr (Experimental and clinical cardiology, 2012)
It has repeatedly been shown that statins decrease morbidity and mortality in patients with atherosclerosis, thus supporting their use for the primary and secondary prevention of ischemic heart disease. Different pathological pathways that are triggered in the setting of acute coronary syndrome (ACS), such as endothelial dysfunction, activation of inflammatory and coagulation cascades, and thrombus formation, are known to be inhibited by statins, thereby justifying the use of these agents in patients with ACS. Several recent prospective controlled clinical trials have demonstrated the safety and, in some cases, the efficacy of statins when administered early after ACS. An increasing number of publications have reported, however, that statins may confer a beneficial effect not only in early secondary prevention, but also in the direct treatment of ACS (ie, when statins are administered as first-line treatment in clinically unstable patients). This therapeutic option is supported by the following: numerous experimental studies demonstrating a protective effect of statins under conditions of acute ischemia; analysis of different registries and trials, which has demonstrated a more favourable prognosis for statin-treated patients at the time of acute myocardial ischemia; and small clinical trials reporting a lower periprocedural infarction rate during coronary intervention or lower levels of several prognostic biomarkers, in addition to a lower incidence of cardiovascular events associated with statin therapy. Nevertheless, confirmation of this hypothesis in large prospective controlled clinical trials will be necessary before the implementation of statins as first-line therapy in unstable patients with ACS, irrespective of blood cholesterol levels.
Keywords: Statin; Myocardial infarction; Acute coronary syndrome